Rat experimental transplantation surgery : a practical guide - Girman, Peter; Kriz, Jan; Balaz, Peter (Springer International Publishing Imprint: Springer, 2015)
The aim of the book is to describe tested microsurgical procedures of kidney, pancreas, islets, heat, liver and small bowel transplantation. All procedures written in the book are used in our experimental research laboratory and their description will be provided by an experienced researcher. The book is organized into 'General' and 'Specific' sections. The 'General' section will include principles, doses and available drugs for rat anaesthesia, the surgical anatomy of the rat, a brief review of immunosuppressant's used in rat models, a description of basic surgical techniques and blood sampling. The 'Specific' section will include a description of the rat model with the appropriate organ failure relevant to the organ transplantation, which will be followed by a detailed description of the surgical procedure with high quality pictures of key steps. Each chapter will describe 'tips and tricks' including practical advice and recommendations.